On Semantic Transformations of Russian Nouns in Language of Commerce and Advertising - E. M. Katsman (Научный диалог, 2017)
Transformations of the semantics of nouns market , package , portfolio , product , formula , care , protection in modern varieties of Russian-speaking discourse associated with commerce and advertising are analyzed. The choice of lexical units is dictated by the frequency of their use in figurative meaning in the advertising and commercial texts. The research urgency is caused by necessity to clarify and supplement the existing lexicographical descriptions in accordance with the continuous process of semantic extension, which is typical to Russian language of early 21st century. By matching vocabulary definitions with usage and with the help of the context analysis the directions and mechanisms of formation of new lexical meanings of the mentioned nouns are traced, many of which were fixed already in the common language, while others represent specific features of the language of advertising. The author comes to the conclusion that some mechanisms of the formation of new meanings in the language of the commercial sector differ from mechanisms typical to the language of advertising, despite the fact that extra-linguistic factors contributing to the formation of these meanings (the strategy of influencing the consumer) have a lot in common.